An Exploration of Growth Mindset in Muslim Student Leadership: A Case Study of the IOU Indonesia Student Committee - Febi Robianti; Mufutau Oyedapo Raufu; Rif’atun Nur Khairani; Humairoh Hasan; Febi Robianti; Mufutau Oyedapo Raufu; Rif’atun Nur Khairani (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
This study explores the development of growth mindset among Muslim student leaders in the IOU Indonesia Student Committee (SC). Using a qualitative case study design, data were collected through written interviews and open-ended questionnaires with 20 board members. Thematic analysis revealed three core themes: Faith-Based Mindset (100%), where all participants grounded resilience and leadership identity in Islamic values such as amanah, tawakkul, and sabr; Leadership as Learning (85%), in which most participants described leadership as an iterative process of mistakes, feedback, and improvement; and Community Support (65%), emphasizing mentorship, peer encouragement, and collective growth as significant sources of resilience. Findings suggest that leadership is deeply constructed through spirituality, strengthened by experiential learning, and sustained by community ties. This integration underscores the importance of culturally and spiritually grounded approaches to fostering resilient and adaptive student leadership.